Behavioral analytics in social and ubiquitous environments : 6th International Workshop on Mining Ubiquitous and Social Environments, MUSE 2015, Porto, Portugal, September 7, 2015; 6th International Workshop on Modeling Social Media, MSM 2015, Florence, Italy, May 19, 2015; 7th International Workshop on Modeling Social Media, MSM 2016, Montreal, QC, Canada, April 12, 2016; Revised Selected Papers /: 6th International Workshop on Mining Ubiquitous and Social Environments, MUSE 2015, Porto, Portugal, September 7, 2015; 6th International Workshop on Modeling Social Media, MSM 2015, Florence, Italy, May 19, 2015; 7th International Workshop on Modeling Social Media, MSM 2016, Montreal, QC, Canada, April 12, 2016; Revised Selected Papers. (2019) - Unknown
No abstract available